Company Financial Performance Before and During the Covid-19 Period in the Pharmaceutical Sub-Sector - Dinulhaq, Rifky; Rudianto, Dudi (International Journal of Entrepreneurship and Business Management, 2023)
The Pharmaceutical Industry generates short-term profits that support the need of handling Covid-19. Based on this explanation, this study aims to determine the company's financial performance before and during the Covid-19 pandemic and compare the company’s financial performance before and during the Covid-19 pandemic in the pharmaceutical sub-sector listed on the IDX for the 2018-2021 period. Research using a purposive sampling method. Thus, 10 samples were obtained from 11 pharmaceutical sub-sector companies. The analysis technique used is the normality test, homogenity test, and paired sample t-test. Statistical calculations use the IBM SPSS Statistics 25 application. The results show that the company's financial performance before and during the Covid-19 pandemic in the pharmaceutical sub-sector as measured using the Current Ratio, Debt to Equity Ratio, and Return On Assets have values that are well above the standard. industrial value. While Total Assets Turnover produces a value that is not good below the industry standard value. So that there are 3 conditions of poor company performance such as INAF, KAEF, and PEHA, while there are 7 good company conditions such as DVLA, KLBF, MERK, PYFA, SCPI, SIDO, and TSPC. Comparison of the Current Ratio, Debt to Equity Ratio, Total Assets Turnover, and Return On Assets before and during the Covid-19 pandemic in the pharmaceutical sub-sector listed on the IDX showed no significant differences partially or simultaneously.